Perfusion CT in Acute Ischemic Stroke: A Qualitative and Quantitative Comparison of Deconvolution and Maximum Slope Approach - Abels, B.; Klotz, E.; Tomandl, B.F.; Kloska, S.P.; Lell, M.M. (American Journal of Neuroradiology, 2010)
BACKGROUND AND PURPOSE: PCT postprocessing commonly uses either the MS or a variant of the DC approach for modeling of voxel-based time-attenuation curves. There is an ongoing discussion about the respective merits and limitations of both methods, frequently on the basis of theoretic reasoning or simulated data. We performed a qualitative and quantitative comparison of DC and MS by using identical source datasets and preprocessing parameters. MATERIALS AND METHODS: From the PCT data of 50 patients with acute ischemic stroke, color maps of CBF, CBV, and various temporal parameters were calculated with software implementing both DC and MS algorithms. Color maps were qualitatively categorized. Quantitative region-of-interest–based measurements were made in nonischemic GM and WM, suspected penumbra, and suspected infarction core. Qualitative results, quantitative results, and PCT lesion sizes from DC and MS were statistically compared. RESULTS: CBF and CBV color maps based on DC and MS were of comparably high quality. Quantitative CBF and CBV values calculated by DC and MS were within the same range in nonischemic regions. In suspected penumbra regions, average CBFDC was lower than CBFMS. In suspected infarction core regions, average CBVDC was similar to CBVMS. Using adapted tissue-at-risk/nonviable-tissue thresholds, we found excellent correlation of DC and MS lesion sizes. CONCLUSIONS: DC and MS yielded comparable qualitative and quantitative results. Lesion sizes indicated by DC and MS showed excellent agreement when using adapted thresholds. In all cases, the same therapy decision would have been made. AIFarterial input functionASPECTSAlberta Stroke Program Early CT ScoreCBFcerebral blood flowCBVcerebral blood volumeDCdeconvolutionGMgray matterLMSleast mean squareMIPmaximum intensity projectionMSmaximum slopeMTTmean transit timeNVTnonviable tissuePCAposterior cerebral arteryPCTperfusion CTrCBFrelative cerebral blood flowrCBVrelative cerebral blood volumerMTTrelative mean transit timerTTDrelative time to drainrTTPrelative time to peakROIregion of interestSNRsignal-to-noise ratioSVDsingular value decompositionTACtime attenuation curveTARtissue at riskTTDtime to drainTTPtime to peakTTStime to startWMwhite matter